ALTERNATIVE INDICATORS OF POWER OF ELECTRIC ENERGY IN A SINGLE-PHASE CIRCUIT WITH POLYHARMONIC CURRENT AND VOLTAGE - O. V. Bialobrzeski (National Technical University "Kharkiv Polytechnic Institute", 2019)
Introduction. Many electrical engineering issues use a power balance. It is compiled from averaged power values, and equivalent power is used to characterize power of transient processes. To account electricity, both mono- and polyharmonic currents and voltages use active and reactive power, the quality of electricity is not taken into account. Problem. A number of works are declared a certain number of power components that reflect indicators of quantity and quality of electrical energy. These components of power are subject to criticism. The order of determining power components requires algorithmization, as well the task of determining indicators that will reflect poor quality of energy. Goal. Development of a technique for determining the components of power in single-phase circuits with polyharmonic current and voltage, for definition electrical energy transmission indicators. Methodology. Based on analysis of power components determined in known papers and order of their calculation, the features of taking sign of sine and cosine orthogonal components are marked, depending on combination of numbers a current and voltage harmonics. Using Fourier theory of series and elements of the logic algebra, an algorithm for determining components of electric power energy is developed. Results. Highlighting active and reactive powers of the fundamental harmonic of current and voltage; active and reactive power; canonical power components; non-canonical power components, and proposed indicators of quality of transmission of electrical energy. Originality. Based on analysis of power represented by trigonometric Fourier series, the specific calculation of canonical and non-canonical components with use of a number of indicators of electric energy transmission is proposed that reflect its quality. Practical value. The proposed power components of transmission of electrical energy can be used in technical accounting systems.